2003
DOI: 10.1128/iai.71.5.2591-2597.2003
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Similarities betweenBordetella aviumand Other Pathogenic Bordetellae

Abstract: Bordetella avium causes an upper respiratory tract disease (bordetellosis) in avian species. Commercially raised turkeys are particularly susceptible. Like other pathogenic members of the genus Bordetella (B. pertussis and B. bronchiseptica) that infect mammals, B. avium binds preferentially to ciliated tracheal epithelial cells and produces similar signs of disease. These similarities prompted us to study bordetellosis in turkeys as a possible nonmammalian model for whooping cough, the exclusively human child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 49 publications
2
21
0
4
Order By: Relevance
“…More recently, however, these same authors have found genes in B. hinzii, B. holmesii, and B. trematum that they had previously reported to be missing (24). Additionally, in B. avium, three genes (fhaB, bvgS, and fimC) that were originally thought to be absent from the genome have also been identified (76). Thus, it was not surprising that in this study we were able to identify cyaA in the B. hinzii chromosome.…”
Section: Discussionmentioning
confidence: 95%
“…More recently, however, these same authors have found genes in B. hinzii, B. holmesii, and B. trematum that they had previously reported to be missing (24). Additionally, in B. avium, three genes (fhaB, bvgS, and fimC) that were originally thought to be absent from the genome have also been identified (76). Thus, it was not surprising that in this study we were able to identify cyaA in the B. hinzii chromosome.…”
Section: Discussionmentioning
confidence: 95%
“…B. avium is a bird pathogen causing coryza and rhinotracheitis in poultry (263,718). B. hinzii is found mainly as a commensal of the respiratory tracts of fowls but has pathogenic potential in immunocompromised humans (171,404).…”
Section: Phylogenetic Relationships Betweenmentioning
confidence: 99%
“…Although B. pertussis has been classically identified as the sole agent responsible for whooping cough, other species (i.e., B. parapertussis and B. holmesii) can also cause coughing that resembles whooping cough (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). B. pertussis is a Gram-negative, pleomorphic aerobic coccobacillus that grows optimally on either Bordet-Gengou or Regan-Lowe agar between 35°C and 37°C and can be differentiated from other Bordetella species based on its growth and biochemical characteristics.…”
Section: Microbiology Of Bordetella Speciesmentioning
confidence: 99%